Sensitive analytical method for particle-bound polycyclic aromatic hydrocarbons: A case study in Chiang Mai, Thailand - Somporn Chantara (2018)
Using a MiniVol air sampler, respirable particulate matter (PM 10) was collected from 4 areas in Chiang Mai City. Concentrations of 16 polycyclic aromatic hydrocarbons (PAHs) in the PM10 samples were determined by extraction from a quartz fibre filter with acetonitrile using an ultrasonicator, before filtering and evaporating prior to GC-MS analysis. The mean 24 h PM10 levels in a suburban area, a community area, and two traffic-congested areas were found to be in the ranges 15-54 μg/m 3, 23-60 μg/m3, and 67-144 μg/m3, respectively. The mean total concentrations of the 16 PAHs in the PM 10 samples were in the ranges 2.7-8.4 ng/m3, 3.9-9.1 ng/m3, and 7.6-16.6 ng/m3, respectively. The amount of PM10 was fairly well correlated with particle-bound PAH concentrations. Temporal variation clearly affected the PM10 concentration but it was not so clear in the case of particle-bound PAHs. The average benzo(a)pyrene-equivalent carcinogenic power values showed that community areas had a better air quality than traffic-congested areas. The diagnostic ratios revealed that diesel engine emissions might be the main source of PAHs in the ambient air of these areas.